Tunable production of elemental Se vs. H2Se through photocatalytic reduction of selenate in synthetic mine impacted brine: engineering a recoverable Se product. Issue 4 (13th February 2023) - Holmes, Andrew B.; Ngan, Aldrich; Giesinger, Kayleanna; Gu, Frank
Abstract : Photocatalytic reduction removes selenium from industrial brine through tunable reduction pathways to either Se0(s) or H2 Se(g) . Abstract : In this paper, we investigate the tunability of Se reduction products (Se0(s) vs. H2 Se(g) ) during the photocatalytic reduction of selenate over TiO2, using formic acid as an electron hole scavenger, in synthetic mine-impacted brines (SMIB). Photocatalytic reduction can effectively remove Se from SMIB to <2 μg L −1 from an initial Se concentration of >3300 μg L −1 in under 10 × 10 19 photons cm −2 . An increase in solution temperature led to a marked increase in selenate removal kinetics and an increase in selectivity towards H2 Se(g), while increasing the concentration of formic acid led to an increase in selenate removal kinetics and a decrease in the selectivity towards H2 Se(g) . A bivariate response surface analysis was used to elucidate the mechanism behind the production of >99% gaseous H2 Se or >85% solid Se 0, under varying reaction conditions. Finally, a two-pronged electron transfer model is proposed to explain the selectivity towards Se0(s) vs. H2 Se(g) under varying conditions: (i) Se0(s) is produced through direct reduction of selenate by TiO2 conduction band electrons and (ii) H2 Se gas is produced through electrons transferred into Se 0, followed by an autocatalytic reduction of Se 0 to H2 Se or through a direct reduction by CO2 ˙ − .